Understanding the roles of modernity, science, and risk in shaping flood management. (3rd March 2015) - Nobert, Sébastien; Krieger, Kristian; Pappenberger, Florian
Abstract : In the face of an unprecedented climate crisis, uncertainties over both the frequency and the magnitude of extreme weather events are positioning the development of scientific and political responses to flood hazards as pivotal to adaptation strategies. While floods are generally understood as the results of hydro‐meteorological processes, their physical nature is also hiding some wider theoretical and practical dimensions that are intrinsically social. In turn, those dimensions unveil floods as social 'revealers', capable to exhibit the central role played by the fusion between science and politics in defining regimes of risk‐based flood governance. From the emergence of numerical weather predictions to the increasing sophistication of meteorological and hydrological predictions, the age‐old threat of flooding is increasingly viewed through a distinctively modern lens, which ultimately aims at organizing, producing, and securing futures by the consolidation of resilient societies. In spite of the considerable research efforts and resources invested into science and risk assessment instruments to underpin a more anticipatory and adaptive strategy to flooding, it is important to recognize that both science and risk politics are framing our capacity to engage with new forms of hazards that cannot be measured or quantified. WIREs Water 2015, 2:245–258. doi: 10.1002/wat2.1075 This article is categorized under: Engineering Water > Planning Water Science of Water > Water Extremes Human Water > Water Governance